Reformist Yahudilik - Tiryaki, Hatice (My University, 2006)
REFORMİST YAHUDİLİK 18. ve 19’yy’ı etkileyen düşünce değişiklikleri Yahudiliği de etkilemiştir. Yahudilerle diğer toplumların kaynaşmasını önleyen dış engeller; özellikle Rönesans, Aydınlanma Hareketi, Fransız Devrimi, gibi değişimlerle yıkılmış; eski dini kurumlarla, yeni toplumsal hayatın, uyum sağlamasına paralel olarak bazı değişiklikler oluşmuştur. Yahudilerin durumlarında meydana gelen değişiklikler yeni liberal akımların doğmasına sebep olmuştur. Tezimizin konusu olan Reformist Yahudilikte bu akımlardandır. Reform özellikle sosyal adalet hakkındaki Peygamberlerin haber verdiklerimesaja önem vermiş ve Yahudiliği daha yüksek bir dünya barışı için evrensel bir amaca hizmet eden bir yere getirmeye çalışmıştır.

REFORM JUDAİSM Thought changes that effected the century of 18 and 19 have also been effected Judaism. Outer barriers effecting other societies and Jews had been destroyed by changes such as Renaissance, Illumination Action and French Revolution and some changes parallel to harmony between old religious establishments and new social life have beenappeared. Changes appeared in status of Jews have caused to birth of new liberal trends. Reform Judaism, the subject of thesis, is from those trends. Reform has paid attention on news of Prophets especially on social justice and tried to bring Judaism to a place serving for universal object to provide higher world peace.
Keywords: Felsefe; Yahudiler; Yahudiler_Reform